Fenomena Pernikahan Anak Usia Dini sebagai Penyimpangan Budaya Indonesia - Chazizah Gusnita (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Indonesia has many cultures that are prone to violence and deviation. This problembecomes an important focus in this study because this cultural’s deviation involved childrenin it. Indonesia has the second highest child marriage rate in ASEAN after Cambodia andranks 37th overall in the world. This study described the circumstances, conditions,situations, events, and activities as well as the support of community leaders in legalizingearly childhood marriage in South Nias as a case study. The phenomenon of early marriageculture in South Nias, especially in Hilinamoniha village, is still happening and has becomea natural and normal thing for the local community. Adat which is still very strong shiftsthe position of the government as the highest peak of power in a village. Traditional leadersas customary holders who give permission for a marriage to take place are the key for thecommunity to continue to be brave and willing to marry off their children must be underage.Parents who marry off their children are also another major factor in the occurrence of earlymarriage. This research uses rational theory with qualitative descriptive method